1998
DOI: 10.1038/sj.mp.4000425
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism within the promoter of the serotonin transporter gene and antidepressant efficacy of fluvoxamine

Abstract: Depression with psychotic features has been shown to respond to selective serotonin reuptake inhibitors (SSRIs). The serotonin transporter (5-HTT) is a prime target for SSRIs. A functional polymorphism within the promoter region of the 5-HTT gene, leading to different transcriptional efficiency, was recently reported. We tested the hypothesis that allelic variation of the 5-HTT promoter could be related to the antidepressant response to fluvoxamine and/or augmentation with pindolol (a serotonin autoreceptors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
336
5
14

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 566 publications
(374 citation statements)
references
References 16 publications
19
336
5
14
Order By: Relevance
“…An initial European investigation showed that among sufferers of major depression, 5-HTTLPR long allele is associated with better response to serotonergic antidepressants. 111 This finding has been followed by several replications in European samples. 112,113 However, findings in Asian and American samples have been inconsistent, including findings of effect in the opposite direction in Korean samples 114,115 and of no association with antidepressant response in a large multicentre USA study.…”
Section: Serotonin Transporter Gene-environment Interaction R Uher Anmentioning
confidence: 71%
See 1 more Smart Citation
“…An initial European investigation showed that among sufferers of major depression, 5-HTTLPR long allele is associated with better response to serotonergic antidepressants. 111 This finding has been followed by several replications in European samples. 112,113 However, findings in Asian and American samples have been inconsistent, including findings of effect in the opposite direction in Korean samples 114,115 and of no association with antidepressant response in a large multicentre USA study.…”
Section: Serotonin Transporter Gene-environment Interaction R Uher Anmentioning
confidence: 71%
“…169 Given that the 5-HTTLPR polymorphism is in the regulatory promoter region of the serotonin transporter gene, it is likely that dynamic endophenotypes, concerning response to a challenge or a stressor will be of greater value in disentangling the mechanism of this G Â E. Promising examples include response to tryptophan depletion, 90,93,94 HPA activation by stress and response to corticosteroids, 71 and clinical response to serotonin reuptake inhibitors. 111 Exploring the interplay between psychological and biological intermediate phenotypes is one way forward to disentangle and characterise the G Â E.…”
Section: Genetic Control Of the Environmentmentioning
confidence: 99%
“…Hardy-Weinberg equilibrium was examined in studies where genotype frequencies were included. 9,[15][16][17][18][19][20][21][22][23][24][25] Given the lack of unequivocal data for 5-HTTLPR genotype pooling, we tested both dominant and recessive hypotheses: l/l versus l/s-s/s and l/l-l/s versus s/s. Outcome was defined with three phenotypes: remission rate, response rate, and response rate within 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Our group performed the first studies, and tested the hypothesis that 5-HTTLPR was related to the response to fluvoxamine and/or augmentation with pindolol in 102 inpatients with major depression. 9 The carriers of the long allele showed a better response to fluvoxamine compared to those who were homozygous for the short allelic variant. Following this pilot study, the association between 5-HTTLPR and response in patients with mood disorder has been investigated by a large number of studies, but findings are not always consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, another reason for the conflicting results could be due to the fact that the polymorphism investigated is in linkage disequilibrium with a nearby functional one. 81 Recently, the SERTPR polymorphism has been associated with the antidepressant response to certain selective serotonin reuptake inhibitors, such as fluvoxamine [82][83][84][85] and paroxetine. 86,87 A possible common mechanism may therefore underlie SSRI and lithium efficacy even if the exact mechanism of action of lithium activity is largely unknown.…”
Section: A Serretti Et Almentioning
confidence: 99%